The Didactic Value Of The Faqiri Divan (Texas Journal of Philology, Culture and History, 2026)
The divan compiled by Faqiri, a poet and representative of the Khorezm Jadid movement, is preserved in the manuscript collection of the Abu Rayhan Beruni Institute of Oriental Studies of the Academy of Sciences of Uzbekistan. This article examines, alongside the ghazals, rubai, and mukhammas contained in the divan, the place, quantity, and significance of other genres - masnavi, musaddas, murabba, and works in different poetic forms written on the same theme. Because this divan was written in Faqiri's own hand, that is, it is an autograph manuscript, it should be regarded as a highly reliable source for studying the ideological and artistic features of the poet's work. The divan reflects the poet's creative output from the late nineteenth century up to 1914-1915 and serves as the main object of this research